Theorists of economic growth from David Humes to the present - Rostow, W.W. (New York, 1990)
A distinguished economist surveys important theorists from Hume and Adam Smith to the present and explores how they chose to deal - or not to deal - with the variables and problems posed by the dynamics of economic growth. Each of the three historical sections is organized differently according to the particular way in which growth theory was treated in each period. A concluding section deals with the unsolved problems of growth theory and the economic agenda facing the world into the next century.
Keywords: Economics